Universal(ly Bad) Service : Providing Infrastructure Services to Rural and Poor Urban Consumers - Clarke, George R. G. (World Bank, Washington, DC, 2014)
Until recently, utility services (telecommunications, power, water, and gas) throughout the world were provided by large, usually state-owned, monopolies. However, encouraged by technological change, regulatory innovation, and pressure from international organizations, many developing countries are privatizing state-owned companies and introducing competition. Some observers worry that even if reforms improve efficiency, they might compromise an important public policy goal-ensuring "universal access" for low-income and rural households. The authors review the motivation for universal service, methods used to try to achieve it under monopoly service provision, how reforms might affect these approaches, and the theoretical and empirical evidence of the impact of reform on these consumers. Next, using household data from around the world, they investigate empirically the historical performance of public monopolies in meeting universal service obligations and the impact of reform. The results show the massive failure of state monopolies to provide service to poor and rural households everywhere except Eastern Europe. Moreover, while the data are limited, the evidence suggests that reforms have not harmed poor and rural consumers, and in many cases have improved their access to utility services. Nevertheless, because competition undermines traditional methods of funding universal service objectives (cross-subsidies), the authors also review mechanisms that could finance these objectives without compromising the benefits of reforms.